Sustainable innovations: Theories, conflicts and strategies - Cordula Kropp (Universität Stuttgart, Institut für Sozialwissenschaften, Abteilung für Organisations- und Innovationssoziologie, 2018)
Sustainable innovations can help to find ways of addressing major challenges such as global warming and resource consumption. This article begins by clarifying the specific inconsistencies within the concept, before introducing the research on sustainability-oriented innovation processes. This research is geared in part towards sustainability innovations in organisations and in part towards overarching processes of societal transformation for sustainable development. The article concludes by discussing strategies for promoting sustainable innovation and drawing consequences for the sustainable rebuilding of infrastructure. – – Nachhaltige Innovationen können dazu beitragen, Antworten auf die großen Herausforderungen wie globale Erwärmung und Ressourcenverbrauch zu finden. Der Beitrag klärt einleitend die spezifischen Widersprüchlichkeiten des Konzepts und führt dann in die Forschung zu nachhaltigkeitsorientierten Innovationsprozessen ein. Diese richtet sich teils auf Nachhaltigkeitsinnovationen in Organisationen und teils auf übergreifende, gesellschaftliche Transformationsprozesse für eine nachhaltige Entwicklung. Abschließend werden Strategien ihrer Förderung diskutiert und Konsequenzen für einen nachhaltigen Infrastrukturumbau abgeleitet.
Keywords: 300